If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + -8) = 3x + 5 Reorder the terms: 2(-8 + 5x) = 3x + 5 (-8 * 2 + 5x * 2) = 3x + 5 (-16 + 10x) = 3x + 5 Reorder the terms: -16 + 10x = 5 + 3x Solving -16 + 10x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + 10x + -3x = 5 + 3x + -3x Combine like terms: 10x + -3x = 7x -16 + 7x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 7x = 5 + 0 -16 + 7x = 5 Add '16' to each side of the equation. -16 + 16 + 7x = 5 + 16 Combine like terms: -16 + 16 = 0 0 + 7x = 5 + 16 7x = 5 + 16 Combine like terms: 5 + 16 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 7x+2=50+x | | 10x=22-x | | y=10+12x-3X^2-2X^3 | | y=10+12x-3X^2-3X^3 | | 2x*2x^3=0 | | -2a^2-ab+b^2=0 | | 6+1.3n=24 | | 5x-8+3x+6=0 | | -(-9j-7w)= | | 7385-67x=1996+43x | | 7385-67x=1996+43 | | 2x*x=5+9x | | 4x^2+12x-60=0 | | [8-2]= | | 2x^2+6x-65=0 | | 5y^2-4y^3-7y^2+7y^3= | | 7-5c=17 | | -[94]= | | 3y^2-3y^3-7y^2+7y^3= | | (1-i)(i-2)= | | 12s+8-3=11s-3 | | 6y^2+3y^2-1624=0 | | 3x+35=11x-61 | | 8x+7=5x-19 | | x^2-3.5x-1=0 | | 5(x-5)+19=-13+2(3x-8) | | 4x*4=12x*2 | | i+(-1+2)=0 | | x+(x+15)+(3x-40)=900 | | (1-i)+(3i-2)=0 | | 30*450= | | (1+i)(i+2)=0 |